A influence of parents attitudes and sosioeconomic status on pupils' academic performance in Mathematics - Abdulkareem, Taofeeq Olarewaju; Yakubu, Francis Moodu; Sulaimon, Jamiu (Universitas Sarjanawiyata Tamansiswa, 2024)
The study investigated the influence of parents’ attitudes and socioeconomic status on pupils’ academic performance in mathematics. A survey research design was adopted. The population of this study consisted of all parents of middle-basic school pupils in Ilorin, south LGEA. As a population sample, a simple random sampling technique was used to select one hundred (100) pupils whose parents are the target population of the study. Ten (10) government and ten (10) private basic schools in the area were randomly selected. In order to represent an adequate representation of the entire population, five pupils from the basic six classes in each of the twenty schools were randomly selected to make a total of one hundred (100). A self-developed, structured questionnaire was used to elicit responses from parents. The instrument was validated by two research experts and tested for reliability using the test rest at a 0.73 coefficient value through Cronbach’s alpha. The academic performance of pupils was limited to their’ mathematics grade scores in a promotion examination. The study was guided by two research questions and one hypothesis. An analysis of multiple regression was used to test the hypothesis at the 0.05 alpha level of significance. The result of the findings therefore revealed that the attitudes and socioeconomic status of parents do not influence pupils’ academic performance in mathematics. It was then recommended that parents who are not educated or have low educational qualifications feel encouraged to enroll their children in remedial summer coaching provided by private bodies during holidays to supplement the regular school program in an attempt to improve academic performance, especially in mathematics. There should also be periodic workshops, seminars, and symposiums for in-service mathematics teachers to keep them abreast of new teaching strategies in science and mathematics.